TOTAL VISCERAL DEBRANCHING IN A PATIENT WITH ATHEROSCLEROTIC THORACOABDOMINAL AORTIC ANEURYSM AND OCCLUSION OF ALL VISCERAL BRANCHES - A. E. Zotikov; A. S. Ivandaev; A. V. Kozhanova; M. М. Abdulgamidov; I. E. Timina; D. I. Maryan (Атеротромбоз, 2018)
This article describes the clinical observation of a patient with an atherosclerotic aneurysm of the thoracoabdominal aorta and the occlusion of all visceral arteries. Taking into account the occlusion of all visceral arteries, we opted for a hybrid method of treatment, which included total visceral debranching followed by endoprosthetics of the thoracoabdominal aorta. The chosen method made it possible to execute an open surgery without any complications.